Thinking of Incentivizing Care? The Effect of Demand Subsidies on Informal Caregiving and Intergenerational Transfers - Joan Costa-Font; Sergi Jimenez-Martin; Cristina Vilaplana-Prieto (Institute of Labor Economics (IZA), 2018)
We study the effect of demand-side subsidies to old age care recipients on both caregiving and intergenerational transfer decisions. We exploit two quasi-natural experiments referring to the inception of a universal and unconditional caregiving allowance in 2007 and its subsequent reduction in 2012. We find that the introduction of a caregiving allowance of a magnitude up to 530 exteuro in 2011 increased the probability of informal caregiving by 32% and the intensity of care in 13.5 days/year. Consistently, we find that downstream (upstream) intergenerational transfers increased (decreased) in a magnitude of 29% (15%). The effects concentrate among middle and lower income households and were attenuated by the reduction of the subsidy.
Keywords: I18; D14; G22; 330; caregiving; intergenerational transfers; unconditional transfer; difference-in-differences; long-term care; family transfers; exchange motivation; caregiving allowances; demand-side cash subsidies